The effectiveness of STRONGkids nutritional screening tool and C-reactive protein in identifying hospital-acquired malnutrition in children - I Gusti Lanang Sidiartha; I Gusti Ngurah Made Suwarba; Ida Bagus Subanada; I Gusti Ayu Putu Eka Pratiwi (Hygeia Press di Corridori Marinella, 2023)
Introduction: Hospital-acquired malnutrition remains high in children and is associated with poor prognoses, such as longer hospital stays and higher mortality. This study investigated the effectiveness of the Screening Tool for Risk on Nutritional status and Growth (STRONGkids) and C-reactive protein (CRP) in predicting hospital-acquired malnutrition in children.  Methods: This observational cohort study was performed in a single tertiary referral hospital between January and October 2020. Children who met the study criteria were recruited on admission and followed until hospital discharge. Their STRONGkids score and blood CRP levels were measured within 24 hours of admission. On discharge, hospital-acquired malnutrition was determined based on a weight loss of 2-5% over 1 week, 5-10% over 1 month, or > 10% over more than 1 month. The associations of STRONGkids scores and blood CRP levels with hospital-acquired malnutrition were assessed using the Chi-square test, considering a significance of p < 0.05.  Results: This study included 109 children, of which 55 (50.5%) were male and 54 (49.5%) were female, with a mean age of 6.1 years. Fifty-one of the 109 children (46.8%) were classified as having hospital-acquired malnutrition. The incidences of hospital-acquired malnutrition in subjects with high-, moderate-, and low-risk STRONGkids scores were 67.6%, 64.7%, and 29.3%, respectively. Subjects with high- and moderate-risk STRONGkids scores were twice as likely to have hospital-acquired malnutrition than subjects with low-risk STRONGkids scores (relative risk [RR] = 2.1; 95% confidence interval [CI]: 1.3-3.6, p < 0.001, and RR = 2.0, 95% CI = 1.0-3.8, p = 0.008, respectively). In addition, the incidences of hospital-acquired malnutrition in children with high and low CRP levels were 68.3% and 33.8%, respectively. This study shows that children with high CRP levels are approximately twice as likely to have hospital-acquired malnutrition than children with low CRP levels (RR = 2.0, 95% CI: 1.3-2.9, p < 0.001). This study's multivariate analysis showed that CRP levels were better predictors of hospital-acquired malnutrition than STRONGkids scores.  Conclusion: The STRONGkids nutritional risk screening tool and blood CRP levels were effective in identifying children at risk of hospital-acquired malnutrition. We recommend that STRONGkids scores and blood CRP levels are routinely measured on admission. CRP levels were better at predicting hospital-acquired malnutrition in children than the STRONGkids nutritional risk screening tool.